Rate of Force Development, Muscle Architecture, and Performance in Young Competitive Track and Field Throwers. - Zaras, Nikolaos D; Stasinaki, Angeliki-Nikoletta E; Methenitis, Spyridon K; Krase, Argyro A; Karampatsos, Giorgos P; Georgiadis, Giorgos V; Spengos, Konstantinos M; Terzis, Gerasimos D (J Strength Cond Res, 2016)
The rate of force development (RFD) is an essential component for performance in explosive activities, although it has been proposed that muscle architectural characteristics might be linked with RFD and power performance. The purpose of the study was to investigate the relationship between RFD, muscle architecture, and performance in young track and field throwers. Twelve young track and field throwers completed 10 weeks of periodized training. Before (T1) and after (T2) training performance was evaluated in competitive track and field throws, commonly used shot put tests, isometric leg press RFD, 1 repetition maximum (1RM) strength as well as vastus lateralis architecture and body composition. Performance in competitive track and field throwing and the shot put test from the power position increased by 6.76 ± 4.31% (p < 0.001) and 3.58 ± 4.97% (p = 0.019), respectively. Rate of force development and 1RM strength also increased (p ≤ 0.05). Vastus lateralis thickness and fascicle length increased by 5.95 ± 7.13% (p = 0.012) and 13.41 ± 16.15% (p = 0.016), respectively. Significant correlations were found at T1 and T2, between performance in the shot put tests and both RFD and fascicle length (p ≤ 0.05). Close correlations were found between RFD, muscle thickness, and fascicle length (p ≤ 0.05). Significant correlations were found between the % changes in lean body mass and the % increases in RFD. When calculated together, the % increase in muscle thickness and RFD could predict the % increase in shot put throw test from the power position (p = 0.019). These results suggest that leg press RFD may predict performance in shot put tests that are commonly used by track and field throwers.
Keywords: Adolescent; Adult; Athletic Performance; Body Composition; Exercise Test; Female; Humans; Male; Organ Size; Physical Conditioning, Human; Quadriceps Muscle; Track and field; Young Adult